Influence of Devices and Technique of Administering a Simple Suspension on the Dosage of STROMECTOL® Tablets - Miyajima, Atsushi; Komoda, Masayo; Sakamaki, Tomomi; Ohtani, Mariko; Yamamoto, Yousuke; Hirota, Takashi; Akagi, Keita; Onuma, Aki; Sugiyama, Natsuko; Matsuda, Keisuke (Iryo Yakugaku (Japanese Journal of Pharmaceutical Health Care and Sciences), 2012)
An oral scabicide, STROMECTOL® Tablets (ivermectin) is often administered to patients as a simple suspension by feeding tube. However, it was reported that the administration by this method was less effective than oral administration of tablets. One reason for this lower efficacy might be that the devices and technique for this method of administration are not appropriate. The aim of this study is to propose an appropriate technique. In this report, we compare the recovery ratio when a simple suspension is pushed through a syringe under various conditions. As a result of washing the syringe with distilled water after the first use, the recovery of ivermectin was higher than that without washing. The recovery of ivermectin from syringes set at an angle of 90° and 45° to the horizon was significantly higher than that at 0° and -45°. And recovery from previously used syringes was about 10% higher than that from new syringes (p<0.05). Furthermore, after having orally administered STROMECTOL® Tablets and gavaged its suspension with an appropriate delivery technique to rabbits, we measured the ivermectin concentrations in plasma by LC-MS/MS. The AUC0-192h of ivermectin was almost equivalent for both methods of administration. In conclusion, to secure the same dosage of administration with a simple suspension as that of tablets, it is highly recommended to employ a previously used syringe at an angle of over 45°, and to inject by a technique that washes out the entire residue in the syringe after first injection.